Electrically tunable graphene metamaterial with strong broadband absorption. (24th November 2020) - Yao, Wei; Tang, Linlong; Nong, Jinpeng; Wang, Jun; Yang, Jun; Jiang, Yadong; Shi, Haofei; Wei, Xingzhan
Abstract: The coupling system with dynamic manipulation characteristics is of great importance for the field of active plasmonics and tunable metamaterials. However, the traditional metal-based architectures suffer from a lack of electrical tunability. In this study, a metamaterial composed of perpendicular or parallel graphene-Al2 O3 -graphene stacks is proposed and demonstrated, which allows for the electric modulation of both graphene layers simultaneously. The resultant absorption of hybridized modes can be modulated to more than 50% by applying an external voltage, and the absorption bandwidth can reach 3.55 μ m, which is 1.7 times enhanced than the counterpart of single-layer graphene. The modeling results demonstrate that the small relaxation time of graphene is of great importance to realize the broadband absorption. Moreover, the optical behaviors of the tunable metamaterial can be influenced by the incident polarization, the dielectric thickness, and especially by the Fermi energy of graphene. This work is of a crucial role in the design and fabrication of graphene-based broadband optical and optoelectronic devices.